Critical Evaluation of Grade 12 English Textbook in Light of National Curriculum Objectives (Journal of Asian Development Studies, 2025)
This study critically evaluates the grade 12 English Book II prescribed by the Punjab Textbook Board, examining its alignment with the national curriculum for English Language grades XI–XII (2006). Using a rubric based on ideological, psychological, and social foundations of curriculum, the analysis highlights a persistent disconnect between the curriculum's competency-based goals. The curriculum emphasises critical thinking, real-life application, and civic engagement, whereas the textbook relies on rote memorisation and surface comprehension. Informed by theorists such as Tyler, Apple, and Eisner, alongside developmental perspectives from Piaget and Vygotsky, the study reveals pedagogical and cognitive misalignments. The textbook promotes a knowledge centred approach, offering limited support for reflective learning, inclusive themes, or performance-based assessment. Similarly, board examinations overlook key language competencies such as speaking, listening, and critical writing. Therefore, this paper suggests a change in the textbook along with the shift in assessment pattern to meet learning objectives. In addition, this theme holds significant importance in educational discourse because textbook evaluation serves as a bridge between curriculum intent and classroom reality. A critical examination of textbook design not only ensures alignment with learning outcomes but also reflects broader social, ethical, and pedagogical commitments of an education system. This study contributes to the ongoing theoretical conversation around curriculum implementation by situating textbook design within the socio-cultural and ideological framework of Pakistani education. Thus, the findings have both theoretical implications for curriculum design and societal implications for equitable and transformative learning.